(untitled) (Applied Biological Research, 2024)
Ebony, a dense black/brown hardwood coming from several species of genus Diospyros, is facing a scarcity in market due to trade ban. This constraint in material availability has led to the adoption of ebonization techniques in other wood, wherein wood is treated to mimic the distinctive dark black colour of ebony. Ebonization process has become an important factor in industries looking for imitated wood products to meet the consumer preferences for aesthetic appeal of ebony-like wood. In this paper a concise insight into the current status of ebony (Diospyros ebenum) in India has been given with emphasis on the ebonization. The paper reviews the effectiveness of various ebonization methods, with focus acetate, as the most promising approach and challenges in this process.